Effect of cooking on the total oxalate content of Taro (colocasia esculenta L Schott) leaves - Gante, Junavie Caladon (College of Home Economics, University of the Philippines Diliman, 2012)
Taro leaves (Colocasia esculenta L Schott) in the Philippines are nutritious, cheap and abundant. However, its potential is limited by its acridity which is caused by inorganic substance called oxalate. In addition, oxalate is also known as an antinutrient for calcium and a main component of kidney stones; thus, its consumption is a health risk. This study aimed to determine the effect of cooking on the total oxalate content of taro leaves. Batches of taro leaves were subjected to different cooking methods (boiling with water, boiling with coconut milk and steaming) using different cooking time (5, 10, 15 and 20 min). The total oxalate content was determined by employing the direct precipitation method. Results showed that locally-cultivated taro leaves contain high amounts of oxalate (814.10 ± 77.79 mg/100g FW). It was found that cooking generally decreases the oxalate content of taro leaves. It was construed that it is best to cook taro leaves in boiling water for 15 min (24.65% oxalate reduction); best to steam for 10 min (8.97%); and best to cook with coconut milk for 5 min (44.85%). In addition, the degree of reduction of oxalate content of taro leaves follows this trend: boiling with coconut milk > boiling with water > steaming. Overall, among the 3 cooking methods utilized, the best cooking treatment that would greatly decrease the oxalate content in taro leaves is boiling with coconut milk.